2016
DOI: 10.1080/1523908x.2016.1265885
|View full text |Cite
|
Sign up to set email alerts
|

The good, the bad, and the statutory: are statutory or non-statutory natural resource management plans higher in quality?

Abstract: The good, the bad, and the statutory: Are statutory or non-statutory natural resource management plans higher in quality? Abstract:Numerous governments around the world have adopted statutory-mandates on plan content based on the assumption that they lead to greater consistency and higher quality of plans. While a number of studies have examined the relationship between mandates to develop plans and plan quality, there has been limited study of the influence of state mandates for plan content on plan quality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Although some studies have demonstrated that outdated plans can have low plan quality scores (Kim et al, 2018;Tang and Brody, 2009), we did not find a relationship between the plan quality overall and reviews (comparing first edition plans and plans that had been revised (t-test = 1.959, p > 0.05). Our results correspond to those reported by Potts (2017) regarding natural resource management plans in two states in Australia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although some studies have demonstrated that outdated plans can have low plan quality scores (Kim et al, 2018;Tang and Brody, 2009), we did not find a relationship between the plan quality overall and reviews (comparing first edition plans and plans that had been revised (t-test = 1.959, p > 0.05). Our results correspond to those reported by Potts (2017) regarding natural resource management plans in two states in Australia.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the increasing attention to environmental planning in recent years, little is known about the quality of plans dealing with environmental issues overall (Berke and Godschalk, 2009). Recent studies have focused on the evaluation of planning documents from specific policy domains such as: climate change (Woodruff and Regan, 2019), natural hazards (Horney et al, 2017), housing (Ramsey-Musolf, 2018), ecosystem services (Cortinovis and Geneletti, 2018), green infrastructure (Kim et al, 2018), natural resource management (Potts, 2017), sustainable development (Conroy and Jun, 2016) and forest resources (Fostera et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, there has been a growing interest among planning scholars in evaluating the quality of a range of plans, especially those focusing on natural hazards [45], ecosystem management [46], climate change [47], and sustainable development [48]. However, there is a lack of common criteria and frameworks for assessing the quality of these plans.…”
Section: Assessment Frameworkmentioning
confidence: 99%
“…In the planning literature, the focus on plans as a text distinct from research studying process, implementation, and outcomes emerged only recently (Guyadeen, 2018;Khakee, 2000;Lyles & Stevens, 2014;Potts, 2017). In the late 1980s, Dear (1986) identified the insufficient examination of planning texts as a stark omission in the planning literature.…”
Section: Studying Comprehensive Planningmentioning
confidence: 99%
“…I selected documents that include preservation in Portland's comprehensive plan, including the Albina Community Plan, and analyzed them through the lens of neo-institutional theory (Alexander, 2005;Healey, 2007). My methodology is grounded in a growing literature that focuses on the plan itself rather than its process, outcome, or implementation (Guyadeen, 2018;Khakee, 2000;Lyles & Stevens, 2014;Neuman, 1998;Potts, 2017).…”
mentioning
confidence: 99%